Additive effects of the Rho kinase inhibitor Y‐27632 and vardenafil on relaxation of the corpus cavernosum tissue of patients with erectile dysfunction and clinical phosphodiesterase type 5 inhibitor failure. (21st November 2016) - Uvin, Pieter; Albersen, Maarten; Bollen, Ine; Falter, Maarten; Weyne, Emmanuel; Linsen, Loes; Tinel, Hanna; Sandner, Peter; Bivalacqua, Trinity J.; De Ridder, Dirk J. M. K.; Van der Aa, Frank; Brône, Bert; et al.
Abstract : Objectives: To evaluate the expression of the Rho/Rho‐associated protein kinase (ROCK) pathway in the corpus cavernosum of patients with severe erectile dysfunction (ED) compared with healthy human corpus cavernosum, and to test the functional effects of two Rho kinase inhibitors (RKIs) on erectile tissue of patients with severe ED, which did not respond to phosphodiesterase type 5 inhibitors (PDE5Is). Patients and Methods: Human corpus cavernosum samples were obtained after consent from men undergoing penile prosthesis implantation ( n = 7 for organ bath experiments, n = 17 for quantitative PCR [qPCR]). Potent control subjects ( n = 5) underwent penile needle biopsy. qPCR was performed for the expression of RhoA and ROCK subtypes 1 and 2. Immunohistochemistry staining against ROCK and α smooth muscle actin (αSMA) was performed on the corpus cavernosum of patients with ED. Tissue strips were precontracted with phenylephrine and incubated with 1 μm of the PDE5I vardenafil or with DMSO (control). Subsequently, increasing concentrations of the RKIs azaindole or Y‐27632 were added, and relaxation of tissue was quantified. Results: The expression of ROCK1 was unchanged ( P > 0.05), while ROCK2 ( P < 0.05) was significantly upregulated in patients with ED compared with controls. ROCK1 and ROCK2 protein colocalized with αSMA, confirming the presence of this kinase in cavernous smooth muscle cells and/or myofibroblasts. After incubation with DMSO, 10 μm azaindole and 10 μm Y‐27632 relaxed precontracted tissues with 49.5 ± 7.42% ( P = 0.1470 when compared with vehicle) and 85.9 ± 10.3% ( P = 0.0016 when compared with vehicle), respectively. Additive effects on relaxation of human corpus cavernosum were seen after preincubation with 1 μm vardenafil. Conclusion: The RKI Y‐27632 causes a significant relaxation of corpus cavernosum in tissue strips of patients with severe ED. The additive effect of vardenafil and Y‐27632 shows that a combined inhibition of Rho‐kinase and phosphodiesterase type 5 could be a promising orally administered treatment for severe ED.